Correlation characteristics of spatial network and driving factors of industrial green water resource efficiency in the Yellow River Basin - SUN Caizhi, SONG Qiangmin, HAO Shuai (Ziyuan Kexue)
[Objective] As a key region in China’s national strategic development, the Yellow River Basin’s sustainable water resource utilization hinges on measuring industrial green water resource efficiency and identifying its spatial spillover effects across upstream, midstream and downstream cities. [Methods] In this study, the Super-SBM model was used to measure the industrial green water resource in 75 cities in the Yellow River Basin from 2006 to 2022, then the correlation structure of the spatial network of efficiency was measured using the SNA model, and finally, the spatial and temporal variance characteristics of the influencing factors were analyzed using the PGTWR model. [Results] (1) The industrial green water resource efficiency in the Yellow River Basin exhibited a fluctuating upward trend, increasing from 0.545 at the beginning of the study period to 0.867 by the end. Spatial disparities within the region were significant, yet inter-regional gaps gradually narrowed, with the middle and lower reaches generally demonstrating higher efficiency values compared to the upper reaches. (2) The intensity of spatial linkages in industrial green water resource efficiency progressively strengthened. Network density exhibited a hierarchical decrease from the lower reaches to the middle and upper reaches. Notable differences in spatial network centrality were observed between the upper reaches and the middle/lower reaches. (3) The impact of various driving factors on industrial green water resource efficiency demonstrated significant spatiotemporal heterogeneity. The degree of openness, population quality, and environmental regulation exhibited significant positive effects on enhancing industrial green water resource efficiency. The level of industrialization exerted the most substantial influence, while per capita water resources imposed a limiting effect on efficiency improvement. [Conclusion] To achieve sustainable water resource utilization and coordinated regional economic development, emphasis should be placed on collaborative development among regions, strengthening linkages between upstream and downstream cities, promoting policy coordination and information sharing among cities within the region, enhancing complementary advantages, and improving cooperation and exchange mechanisms.